The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1469-8137.2011.03867.x
|View full text |Cite
|
Sign up to set email alerts
|

A chloroplast envelope membrane protein containing a putative LrgB domain related to the control of bacterial death and lysis is required for chloroplast development in Arabidopsis thaliana

Abstract: Summary A protein encoded by At1g32080 was consistently identified in proteomic studies of Arabidopsis chloroplast envelope membranes, but its function remained unclear. The protein, designated AtLrgB, may have evolved from a gene fusion of lrgA and lrgB. In bacteria, two homologous operons, lrgAB and cidAB, participate in an emerging mechanism to control cell death and lysis. We aim to characterize AtLrgB using reverse genetics and cell biological and biochemical analysis. AtLrgB is expressed in leaves, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 77 publications
1
36
0
Order By: Relevance
“…Tissue was available from a mutant in the chloroplast polynucleotide phosphorylase, which has a major role in maturing mRNA and rRNA 3′ ends but also participates in RNA degradation through exonucleolytic digestion and polyadenylation (41). We obtained a second mutant that was affected in the gene encoding a chloroplast envelope membrane protein containing a putative LrgB domain, which has been reported recently to play an important role in A. thaliana chloroplast development (42). Examination of the editing extent in two null mutants of the genes encoding these plastid proteins shows no difference from the WT in the editing extent of nad6-161 and cob-325, two mitochondrial sites that show a drastic reduction of editing extent in rip1 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue was available from a mutant in the chloroplast polynucleotide phosphorylase, which has a major role in maturing mRNA and rRNA 3′ ends but also participates in RNA degradation through exonucleolytic digestion and polyadenylation (41). We obtained a second mutant that was affected in the gene encoding a chloroplast envelope membrane protein containing a putative LrgB domain, which has been reported recently to play an important role in A. thaliana chloroplast development (42). Examination of the editing extent in two null mutants of the genes encoding these plastid proteins shows no difference from the WT in the editing extent of nad6-161 and cob-325, two mitochondrial sites that show a drastic reduction of editing extent in rip1 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, PLGG1 was identified as a chloroplast protein in proteomic studies. It was originally thought to be involved in programmed cell death, but current evidence now suggests that this phenotype was linked to the accumulation of photorespiratory intermediates (Yang et al, 2012;Pick et al, 2013). However, the Arabidopsis plgg1-1 line showed neither differences in the quantum efficiency of CO 2 assimilation nor changes in the photorespiratory CO 2 compensation point compared with wild type under lowlight conditions (Walker et al, 2016a).…”
Section: Introductionmentioning
confidence: 90%
“…They showed that the A. thaliana LrgAB protein can augment nystatin-induced cell permeability when produced in yeast (69). This and other observations led another research group to suggest a role in the induction of programmed cell death of chlorotic cells (72).…”
Section: Cidab/lrgab Homologues In Plant Chloroplastsmentioning
confidence: 97%